Laparoscopically Assisted Vaginal Hysterectomy: Analysis of 35 Consecutive Cases - Suat Dede; Berna Dilbaz; Müberra Koçak; Hülya Dede; Serdar Dilbaz; Ali Haberal (Medical Network, 2006)
OBJECTIVE: The aim of this study was to ev aluate indications, effectiv eness and safety of laparoscopically assisted v aginal hysterectomy f or benign adnexal or uterine pathologies. STUDY DESIGN: We rev iewed the records of 35 consecutive women who underwent laparoscopically assisted v aginal hysterectomy f or benign reasons between January 2002 and December 2004. All the patients were not suitable candidates for abdominal or vaginal hysterectomy either because of concomitant adnexal masses or lack of uterine prolapse. The exclusion criteria included prolapse, uterine or adnexal neoplasm, pelv ic inflammation, vaginal stenosis and any pathology with a uterine size of more than 14 weeks. RESULTS: Indications for laparoscopically assisted v aginal hysterectomy were leiomyoma uteri (45.7%), intractable uterine bleeding (17.1%), myoma uteri with adnexal masses (14.3%), postmenopausal (8.6%) or bilateral (8.6%) adnexal masses and tamoxifen related endometrial pathology (5.7%). Mean operating time was 149.31 minutes (range 90-210) and the mean postoperative hospital stay was 2.4 days (range 2-10). Only one bladder laceration occurred during the operations which required conv ersion to laparotomy (2.8%). CONCLUSION: Laparoscopically assisted vaginal hysterectomy was f ound as a f easible and safe approach in the surgical management of a selected group of patients with benign pathologies.